3(x-7)=3x-7(7-x)

Simple and best practice solution for 3(x-7)=3x-7(7-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-7)=3x-7(7-x) equation:


Simplifying
3(x + -7) = 3x + -7(7 + -1x)

Reorder the terms:
3(-7 + x) = 3x + -7(7 + -1x)
(-7 * 3 + x * 3) = 3x + -7(7 + -1x)
(-21 + 3x) = 3x + -7(7 + -1x)
-21 + 3x = 3x + (7 * -7 + -1x * -7)
-21 + 3x = 3x + (-49 + 7x)

Reorder the terms:
-21 + 3x = -49 + 3x + 7x

Combine like terms: 3x + 7x = 10x
-21 + 3x = -49 + 10x

Solving
-21 + 3x = -49 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-21 + 3x + -10x = -49 + 10x + -10x

Combine like terms: 3x + -10x = -7x
-21 + -7x = -49 + 10x + -10x

Combine like terms: 10x + -10x = 0
-21 + -7x = -49 + 0
-21 + -7x = -49

Add '21' to each side of the equation.
-21 + 21 + -7x = -49 + 21

Combine like terms: -21 + 21 = 0
0 + -7x = -49 + 21
-7x = -49 + 21

Combine like terms: -49 + 21 = -28
-7x = -28

Divide each side by '-7'.
x = 4

Simplifying
x = 4

See similar equations:

| 3r*2r= | | B/13-3b/13=8/23 | | -x^2+6x+34=0 | | -0.3(x-4)+x=1.5+-0.5x | | 6x*4x= | | -6(-17)= | | -397h=16t^2 | | ((5/8)x^2)-8x+72.5=0 | | (5a)2= | | 18x+30= | | 4y+9=-7 | | (5/8)x^2-8x+72.5=0 | | 16=2x+2(x-2) | | v-8=3 | | x^2-x+1/4=x/4 | | x^2-6x+9+y^2+2y+1=32 | | 8d-1/3(6-9d)=42 | | 6x+4(x-3)=48 | | 3*3.14d=12*3.14 | | ln(y)=.63 | | h(3)=400-16t^2 | | 7n-2=6n-2n | | (f+4)/2=5 | | 49k^2x-16y-16x+49k^2y=0 | | 12b=-144 | | 5a-(8-a)=4a-10 | | 4(x-7)-3x=3(2x-6) | | (3x-5w)(8x+5w)=0 | | -3(x-2)=5(2x-1) | | 2x+20+60+70=360 | | 12x^2+7xy-10y^2=0 | | ax+b=cox+d |

Equations solver categories